Enzyme Linked Immunosorbent Assay (ELISA) Technique Guideline - Rachmat Hidayat; Patricia Wulandari (HM Publisher, 2021)
ELISA (Enzyme-linked immunosorbent assay) is a technique used to assess the quantification of peptide, protein, antibody and hormone levels, based on the principle of antigen-antibody binding. In the ELISA technique, antigen immobilization will be carried out on a solid surface, then bound with antibodies to form an antigen-antibody bond complex, where the antigen-antibody complex is bound to the enzyme. The detection signal in the form of a color change will be formed due to the reaction between the enzyme and the substrate.